2014
DOI: 10.5935/abc.20140031
|View full text |Cite
|
Sign up to set email alerts
|

Duke Activity Status Index for Cardiovascular Diseases: Validation of the Portuguese Translation

Abstract: BackgroundThe Duke Activity Status Index (DASI) assesses the functional capacity of patients with cardiovascular disease (CVD), but there is no Portuguese version validated for CVD. ObjectivesTo translate and adapt cross-culturally the DASI for the Portuguese-Brazil language, and to verify its psychometric properties in the assessment of functional capacity of patients with CVD. MethodsThe DASI was translated into Portuguese, then checked by back-translation into English and evaluated by an expert committee. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 21 publications
6
45
0
12
Order By: Relevance
“…; Coutinho‐Myrrha et al . ). Long‐term reliability looking at patients in the pre‐dialysis stage and patients who have received a kidney transplant (n = 23) reported that test–retest reliability was in fact higher (0.81) for patients with lower eGFR scores of 15–34 ml/min/1.73 m 2 compared with patients with eGFR scores of 35–59 ml/min/1.73 m 2 whose respective ICC was 0.71 (Ravani et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Coutinho‐Myrrha et al . ). Long‐term reliability looking at patients in the pre‐dialysis stage and patients who have received a kidney transplant (n = 23) reported that test–retest reliability was in fact higher (0.81) for patients with lower eGFR scores of 15–34 ml/min/1.73 m 2 compared with patients with eGFR scores of 35–59 ml/min/1.73 m 2 whose respective ICC was 0.71 (Ravani et al .…”
Section: Discussionmentioning
confidence: 97%
“…Whilst the DASI questionnaire is often used in clinical practice and research for patients with CKD, to date there has only been one test-retest reliability study in this population (Ravani et al 2012;Coutinho-Myrrha et al 2014). Long-term reliability looking at patients in the pre-dialysis stage and patients who have received a kidney transplant (n = 23) reported that test-retest reliability was in fact higher (0.81) for patients with lower eGFR scores of 15-34 ml/min/1.73 m 2 compared with patients with eGFR scores of 35-59 ml/min/1.73 m 2 whose respective ICC was 0.71 (Ravani et al 2012).…”
Section: Test-retest Reliability For Physical Function Measures In Pamentioning
confidence: 99%
“…A higher score represents better functional capacity. The instrument is validated in Portuguese [24].…”
Section: Measurement Of Secondary Outcomes Functionalitymentioning
confidence: 99%
“…("Você tem risco de ter diabetes tipo 2? "), da Sociedade Americana de Diabetes, adaptado (15) , que passou por processo de tradução e adaptação cultural, seguindo sugestões (16,17) para a validação e utilização do questionário proposto. A versão original do questionário (Figura 1) foi traduzida para o português de forma independente, gerando duas versões.…”
Section: Métodosunclassified